Plant Wealth in the Life and Economy of the Tharus of Nainital District, Uttar Pradesh - Singh, K. K.; Maheshwari, J. K. (Indian Forester, 1990)
The forest areas of Nainital district inhabited by the Tharus were explored to study the plant wealth potential of the area The economic plant wealth plays a vital and significant role in the economy and health care system of the tribals An inventory of two hundred plants and plant produce used by the Tharus for food, fibre, medicine, oils, handicrafts, fuels, etc, has been prepared There is enormnus potential to develop the plant-based cottage industries in the tribal tracts of the district such as herbal drug industry, edible plant processing and preservation units, tannins, gum and resin collection, handicrafts and cordage, brooms, mats and basket industry, oilseeds collection and extraction units etc. for the uplift of the tribal and rural population of the district.